Erratum: Fungal infection in lung transplant recipients in perioperative period from one lung transplant center - Qiao, Weizhen; Zou, Jian; Ping, Fengfeng; Han, Zhenge; Li, Lingling; Wang, Xiuzhi (Journal of Thoracic Disease, 2019)
This article that appeared on Page: 1554-1561, Vol 11, No 4 (April 2019) Issue of the Journal of Thoracic Disease (JTD) (1), a mistake occurred in the name of a disease. The “Cystic fibrosis” should be modified to “Interstitial lung disease” in the paper. Additionally, some minor changes have also been made in Table 1. The corrected Table 1 is shown below. However, the conclusions did not change.